Model characteristics of temporal structure of walking, typical for 6–8 year-old children - Kholodov, Serhii (Journal of Education, Health and Sport, 2017)
Topicality. Analysis of social and cultural as well as educational trends points to the fact that various aspects of the younger generation’s motility are the object of experts’ particular attention and the subject of interdisciplinary research. According to many experts, the study of the human movement biomechanics provides extensive material for understanding physiological and nervous processes that determine functioning of the locomotion management system. The task of the research is to develop model characteristics of walking phases of almost healthy children, aged 6–8 years. Research methods include analysis of scientific and methodical resources as well as documentary materials, video-metrics, BioVideo application package, methods of mathematical statistics. Research results. Modelling of walking phases of almost healthy 6-8 year-old children was based on the principles of information sufficiency, feasibility, multiplicity of models and aggregation. Model characteristics have been developed according to time indicators of the walking phases, characteristic for almost healthy children, aged 6–8 years. Since the samples of duration for each walking phase have corresponded to the law of normal distribution, the lower and upper limits of the confidence interval for the arithmetic general mean by the value of the arithmetic average mean of the sample with a confidence probability of 95% were chosen as model characteristics. Conclusion. As a result of the conducted research, the structure of the walking cycle of almost healthy children, aged 6–8 years was studied, the significance of which was confirmed by objective model time indicators. The need to use models and modelling, especially mathematical, is determined by the possibility to solve complex research problems with their help, to forecast and optimize technological processes during physical education of various population groups.